Challenges in Adopting a Constructivist Teaching Approach in a School - Kirtikar, Rushikesh (JOURNAL OF INDIAN EDUCATION, 2021)
The adoption of constructivist approach marks a paradigm shift in school education in India and is still in its early stages of implementation. We need to overcome a number of challenges in its smooth implementation over a large mass of children to attain a quality education for all. The present paper is based on a qualitative academic research and has studied a constructivist school setting in order to understand some of its challenges in implementation in the classroom. It argues how some of the impediments in its smooth application come from the larger curricular structure itself and the limitations posed by syllabus, subjects, timetable and the classroom itself and why it is necessary to restructure our basic curricular components in order to provide a more supportive curricular environment for constructivism to flourish.